High Frequency of Symptomatic Zinc Deficiency in Infants in Northern Ethiopia - Federica Dassoni; Zerihun Abebe; Federica Ricceri; Aldo Morrone; Cristiana Albertin; Bernard Naafs (Hindawi Limited, 2014)
Background. Zinc deficiency occurs in infants when its demand exceeds its supply. It presents with cutaneous signs which, in severe cases, are associated with diarrhea, alopecia, and irritability. Genetic and acquired forms of zinc deficiency have been reported and often overlap clinical features. Malnutrition, prematurity, malabsorption syndromes, and burns may cause an increased demand for zinc. Methods. Cases of acquired transient infantile zinc deficiency (TIZD) observed during a period of 3 years at Ayder Referral Hospital of Mekelle, Northern Ethiopia, are reported here. Since no sophisticated tests were available at our center, the diagnosis was based on the clinical signs and prompt response to oral zinc supplementation. Results. We observed 18 cases of TIZD at our center. All patients were full-term and breastfeeding infants with no relevant associated diseases. Conclusions. In this region, a high incidence of this condition is observed. We could not rule out whether heterozygosity for the genetic mutation was present or that the disease was caused by a nutritional deficiency in the mothers or more probably because both the factors coexisted together. However, further studies are necessary to better understand the causes of the increased incidence of this disease in Northern Ethiopia.